2013
DOI: 10.1161/strokeaha.113.001624
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Sex-Specific Associations Between Systolic Blood Pressure and the Risk of Cardiovascular Disease

Abstract: In 2000, more than a quarter of the world's adult population, totaling nearly 1 billion people, were estimated to have hypertension-a figure that is projected to increase to 29% (1.5 billion) in 2025. 5 Worldwide, it is the leading risk factor for cardiovascular disease (CVD) and accounts for >13% (7 million) of deaths each year, as well as a substantial amount of disability. 1These estimates of disease burden are based on the assumption that the association between systolic blood pressure (SBP) and CVD does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 52 publications
5
74
2
3
Order By: Relevance
“…Since women generally e at a given age e have a lower absolute risk for CVD, the same risk difference associated with a risk factor in each sex would translate into a higher relative effect in women. However, we have previously shown that the detection of a sex difference is neither inevitable [6,7,30], nor upon using relative risks to compare the sex-specific associations between risk factors and outcomes [2]. Thus, our current findings that the relative effects of high total cholesterol on CVD outcomes are largely similar between men and women are unlikely to be as a result of using relative rather than absolute measures of risk.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Since women generally e at a given age e have a lower absolute risk for CVD, the same risk difference associated with a risk factor in each sex would translate into a higher relative effect in women. However, we have previously shown that the detection of a sex difference is neither inevitable [6,7,30], nor upon using relative risks to compare the sex-specific associations between risk factors and outcomes [2]. Thus, our current findings that the relative effects of high total cholesterol on CVD outcomes are largely similar between men and women are unlikely to be as a result of using relative rather than absolute measures of risk.…”
Section: Discussionmentioning
confidence: 56%
“…However, recent metaanalyses have reliably shown that there are clinically meaningful sex differences in the relationships between some risk factors and the risk of CHD and stroke, with stronger effects in women than in men for smoking and diabetes [2e5]. However, stronger excess relative risks in women are not inevitable: elevated levels of systolic blood pressure and body mass index were found to have equally deleterious effects on the risk of CHD and stroke in both sexes [6,7]. Whether a sex difference exists for the association between total cholesterol and CHD and stroke has never been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is a well-known major classical risk factor for the development of CVD. This was again emphasized in a recent meta-analysis including 1.2 million individuals, which reported a 15% increased risk of CHD and 25% increased risk of stroke in both men and women with every 10 mmHg increase in systolic BP, after adjustment for (sex-specific) confounders (47). Furthermore, a reduced glomerular filtration rate (GFR) is associated with an increased CVD risk in high risk populations such as patients with diabetes and hypertension (48).…”
Section: Discussionmentioning
confidence: 99%
“…Also, hypertensive women had a lower risk of stroke and myocardial infarction than men but had a higher risk of developing heart failure with preserved ejection fraction [119]. However, Peters et al show that systolic blood pressure is not associated with higher risks of stroke or ischemic heart disease in one sex versus the other [124]. A review of randomized clinical trials by Turnbull et al concluded that differential hypertension treatment for men and women is unnecessary [125] because the efficacy of the various classes of pharmacological therapies (see ‘2014 Evidence-based Guidelines’ above) to prevent adverse cardiovascular events is similar in both populations [125].…”
Section: Female-specific Diagnosis and Treatmentmentioning
confidence: 99%